2018
DOI: 10.1186/s12882-018-1106-z
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular lymphoma forming massive aortic tumors complicated with sarcoidosis and focal segmental glomerulosclerosis: a case report and literature review

Abstract: BackgroundIntravascular large B-cell lymphoma (IVLBCL) is a rare subtype of extranodal diffuse large B-cell lymphoma characterized by proliferation of B cells within small vessels. Herein, we report a case of a 77-year-old man who presented with IVLBCL and massive tumor formation on the aortic wall who was previously diagnosed with sarcoidosis and focal segmental glomerulosclerosis (FSGS). To our knowledge, this is the first reported case of an IVLBCL with aortic tumor formation.Case presentationA 77-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The current study highlights the importance of blood urea nitrogen and creatinine levels. The results of one study indicated that swollen retroperitoneal lymph node enlargement causes ureteral obstruction or adverse reactions to nephrotoxic chemotherapy drugs as their level increases[ 3 ]. An intermediate relationship between LDH and lymphoma has been reported in the literature, and high LDH indicates a high turnover rate of lymphoma cells and the release of degradation products into the blood (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current study highlights the importance of blood urea nitrogen and creatinine levels. The results of one study indicated that swollen retroperitoneal lymph node enlargement causes ureteral obstruction or adverse reactions to nephrotoxic chemotherapy drugs as their level increases[ 3 ]. An intermediate relationship between LDH and lymphoma has been reported in the literature, and high LDH indicates a high turnover rate of lymphoma cells and the release of degradation products into the blood (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some reported cases involving adhesion of malignant lymphoma to the aorta, surgical treatment was required. These reports note that invasion of the aorta by lymphoma may cause aortic disease 2,[5][6][7][8] . Alexander et al and Matthew et al reported that ectopic lymphoma cells in the aortic wall may cause degeneration of the vessel wall and promote the development of aortic aneurysm 6,9) .…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al and Matthew et al reported that ectopic lymphoma cells in the aortic wall may cause degeneration of the vessel wall and promote the development of aortic aneurysm 6,9) . In addition, Oda et al reported that tumor cells may have affinity to arteriosclerotic lesions because they appeared not only in the aortic aneurysm but also in the arteriosclerotic parts without a visible mass 7) . Some other studies have reported that the malignant lymphoma sometimes causes aortic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation